Copper-catalyzed oxidative decarboxylative coupling of α-keto acids and sulfoximines - Chaleena Pimpasri (2018)
© 2017 The Royal Society of Chemistry. A copper-catalyzed oxidative decarboxylative coupling of α-keto acids with NH-sulfoximines has been developed. With CuBr as the catalyst and K2S2O8as the oxidant, this reaction enables the formation of a C-N bond and gives N-aroylsulfoximine products in moderate to excellent yields. The reaction mechanism is likely to involve the generation of a reactive aroyl radical intermediate.